Factors associated with level of spiritual well-being in female cancer patients in clinical remission in Hospital Universiti Sains Malaysia : a cross sectional study - Thyagarajan, Dandaithapani (2016)
Background: Spiritual well-being (SWB) is believed to be an important component in ensuring better quality of life in cancer patient and incorporating SWB into clinical practice has been given more emphasis in recent years. Objectives: This study examines the relationship between anxiety and depression with SWB and its domains, and other associated factors, among female cancer patients who are in remission. Methods: A total of 150 female cancer patients who are in remission for at least 6 months, were recruited from the out-patient oncology clinic of Hospital Universiti Sains Malaysia (HUSM). Anxiety and depression, and level of spiritual well-being were assessed using the Hospital Anxiety and Depression Scale (HADS) – Malay Version and the Spiritual Well-Being Scale (SWBS) – Malay version, respectively. Other possible associated demographic and clinical factors data were obtained using the Patient’s Data Sheet. The relationship between level of SWB and associated factors were analyzed using the Multiple Linear Regression (MLR), controlling possible confounding factors. Results: One hundred and fifty complete data sets were obtained. There is a significant negative correlation between anxiety score and overall SWB score (p= 0.200) and EWB (p<0.001), but no significant correlation with RWB. Employment showed a significant positive correlation with overall SWB (p<0.001), EWB (p<0.001) and RWB (p<0.001). However, there were no significant correlation found between depression score and other demographic factor. Conclusion: This study found that anxiety and employment is significantly associated with spiritual well-being but depression and other demographic factors has no impact on the spiritual well-being of female cancer patients who are in remission.